Moisture-Responsive Graphene Actuators Prepared by Two-Beam Laser Interference of Graphene Oxide Paper - Jiang, Hao-Bo; Liu, Yan; Liu, Juan; Li, Shu-Yi; Song, Yun-Yun; Han, Dong-Dong; Ren, Lu-Quan (Frontiers in Chemistry, 2019)
Here, we reported an ingenious fabrication of moisture responsive graphene-based actuator via unilateral two-beam laser interference (TBLI) treatment of graphene oxide (GO) papers. TBLI technique has been recognized as a representative photoreduction and patterning strategy for hierarchical structuring of GO. The GO paper can be reduced and cut into grating-like periodic reduced graphene oxide (RGO) microstructures due to laser ablation effect. However, the lower light transmittance of the thick GO paper and the corresponding thermal relaxation phenomenon make it impossible to trigger complete reduction, leading to the formation of the anisotropic GO/ reduced GO (RGO) bilayer structure. Interestingly, the RGO side that feature lower OCGs and higher roughness shows strong water adsorption due to the formation of micronanostructures. Due to the different water adsorption capacities of the two sides, a flower moisture-responsive actuator has been fabricated, which exhibits “opening” and “closing” behavior under different humidity conditions.